The Right to Vote Politics and the Passage of the Fifteenth Amendment - Gillette, William (Johns Hopkins University Press, 2019)
Originally published in 1965. The Right to Vote covers the immediate background, passage, and ratification of the Fifteenth Amendment. Gillette contends that the Fifteenth Amendment was intended to give voting rights to African Americans in the north, sidelining those in the south. African American suffrage, in other words, had the pragmatic effect of bringing power to the Republicans of the north. In short, the Fifteenth Amendment was not a radical document but rather was pushed by Republican moderates in an effort to consolidate their power.